Studie průběhu nákupní činnosti ve vybraném podniku - Šebesta, Radek (Vysoké učení technické v Brně. Fakulta podnikatelská, 2015)
Bakalářská práce se zabývá problematikou dodavatelsko-odběratelských vztahů. Konkrétně je zaměřena na řízení kvality dodavatelů z pohledu konkrétního odběratelského podniku. Práce obsahuje analýzu současného stavu a návrh změn v oblasti vztahů s dodavateli, které mají za cíl zvýšení dodavatelské kvality.

Bachelor thesis deals with customer-supplier relationships. Specifically, it focuses on the quality control of suppliers from the perspective of a buyer of a particular company. The work includes analysis of the current state and design changes in relations with suppliers, aimed at increasing the quality of supply.
The Study of Passing During the Purchasing Activities of the Chosen Company
Keywords: dodavatelé; hodnocení dodavatelů; nákup; dodací termíny; suppliers; evaluation of suppliers; purchase; delivery dates